PENDIDIKAN MULTIKULTURAL DI PONDOK PESANTREN : Sebagai Strategi dalam Menumbuhkan NilaiKarakter - Heri Cahyono (AT-TAJDID, 2017)
Indonesia as a country that has a wide range of cultural, ethnic, religious and economic backgrounds are different, plurality on the one hand provide the social power, but on the other hand is a challenge when it is not properly managed.Islamicboarding school as an educational institution that has a history of nation-building in Indonesia, ofcourse can be a forum in implementing multicultural education in the face of diversity.This paper describes the multicultural education at Islamic boarding school as a strategy to fostering thesocial soul in diversity.In its implementation does not distinguish from each other ranging from groups such as gender, ethnicity, race, culture, social background through treatment. Multicultural education has been stressed to the students in order to develop the potential and capacity to the maximum as it requires no special spaces in themselves and their environment.Keyword: Education, Multicultural, Islamic Boarding School